PENGGUNAAN MEDIA JARIMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG CEPAT DALAM PERKALIAN PADA ANAK TUNANETRA TOTALLY BLIND DI SKH MATHLA’UL ANWAR - Lusiana Lusiana; Neti Asmiati (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2019)
ABSTRACT This study aims to assist in learning mathematics by using Jarimatika media to improve rapid numeracy skills in multiplication of totally blind blind children. The method used is an interview with the teacher and direct interaction with the child. While the material used is 3 boards Imprabroad board, sufficient nails for braille numbers to arise, the board is used as much as 3, namely to anticipate that the spikes do not break through / make the wound around, and use smooth material to form the fingers to touch. At the first experimental phase of Jarimatika media which was made ½ of the imprabroad board, the braille writing was too close and there was no space because the board that was too small made the child when reading what should be 2 instead of 24 because the space was lacking, at the second trial stage using the imprabroad 2x greater than the first trial stage, the space has been greatly improved. This Jarimatika media if it is taught that this continuous media is multifunctional in addition, subtraction, multiplication, and division can be done. but for this time I put more emphasis on multiplication. Because the media is made of tacks and is shaped by the shape of 10 fingers arises to facilitate the process of perforation and the basis is given to declare true or not from the results that have been given. Thus it can be concluded that the use of jarimatika media can increase the ability to quickly calculate the multiplication of totally blind blind children at SMALB X at SKH Mathla'ul Anwar Menes.